Light emitting diode epitaxial structure and preparation method thereof

By setting up an aluminum gallium nitride barrier layer in the epitaxial structure of the light emitting diode, the leakage channel problem caused by defects during growth on heterogeneous substrates is solved, and lower leakage current and higher stability and quality are achieved.

CN119836063APending Publication Date: 2025-04-15CHANGSHA SEMICON TECH & APPL INNOVATION RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411807851.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When the existing gallium nitride-based light-emitting diode epitaxial structure grows on heterogeneous substrates, there are many defects that lead to an increase in leakage channels, a decrease in brightness, a weakened reverse voltage resistance, and a shorter aging life.

Method used

A barrier layer is provided between the unintentionally doped layer and the N-type semiconductor layer. The barrier layer is an aluminum gallium nitrogen layer. The molar amount of aluminum is 26.5% of the total molar amount of aluminum and gallium to prevent defects such as dislocations and reduce leakage channels.

Benefits of technology

It significantly reduces the leakage current of the light emitting diode, improves working stability and quality, and is also highly compatible with process and is easy to promote and apply.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836063A_ABST
    Figure CN119836063A_ABST
Patent Text Reader

Abstract

The invention relates to a light-emitting diode epitaxial structure and a preparation method thereof, and belongs to the technical field of semiconductors. The light emitting diode epitaxial structure comprises a substrate, a nucleating layer, an unintentional doping layer, an N-type semiconductor layer, a multi-quantum well active layer and a P-type semiconductor layer, the nucleating layer, the unintentional doping layer, the N-type semiconductor layer, the multi-quantum well active layer and the P-type semiconductor layer are sequentially stacked on the substrate, a barrier layer is arranged between the unintentional doping layer and the N-type semiconductor layer, and the barrier of the barrier layer to electrons is higher than the barrier of the unintentional doping layer to electrons. And meanwhile, upward propagation of dislocation and other electric leakage channels can be effectively blocked. According to the light-emitting diode epitaxial structure, the number of electric leakage channels is small, the leakage current is small, the preparation process is simple, and application and popularization are easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a light emitting diode epitaxial structure and a preparation method thereof, and in particular to a gallium nitride-based light emitting diode epitaxial structure and a preparation method thereof, and belongs to the technical field of semiconductors. Background Art

[0002] Compared with other light sources (such as incandescent lamps, halogen lamps, etc.), light-emitting diodes have advantages such as long life, low power consumption, fast response speed, and environmental friendliness. They have become the mainstream light source in traditional lighting, landscape lighting, LCD backlighting and other fields, and are also the development direction of the next generation of micro-display technology. Based on III-nitride light-emitting diodes, by using indium gallium nitride (InGaN) or aluminum gallium nitride (AlGaN) as the quantum well active region, continuously adjustable light-emitting devices from deep ultraviolet to red light bands have been realized. Among them, the external quantum efficiency of InGaN blue light-emitting diodes and green light-emitting diodes exceeds 80% and 50% respectively, and are widely used in white light lighting, landscape lighting, large-scale displays and other fields.

[0003] Taking gallium nitride (GaN) light-emitting diodes as an example, its epitaxial structure includes a nucleation layer, an unintentional doping layer (u-GaN), an n-type semiconductor layer (n-GaN), a multi-quantum well layer, and a p-type semiconductor layer (p-GaN) layer stacked in sequence. The above structure grows on a substrate. The basic structure is as follows Figure 1 As shown. Since GaN homogeneous substrates are expensive and small in size, most of the epitaxial structures of GaN light-emitting diodes are currently grown on heterogeneous substrates. During the heterogeneous epitaxy process, the lattice mismatch and thermal mismatch are large, and there are a large number of defects at the interface between the substrate and GaN, such as dislocations and stacking faults. Although the defects will be partially annihilated as the GaN epitaxial film thickens, a large number of defects will continue to propagate upward, thus becoming leakage channels for light-emitting diode devices, resulting in a decrease in the brightness of the light-emitting diode, a decrease in reverse withstand voltage, a shortened aging life, poor anti-static breakdown capability, low energy conversion efficiency, red shift of the emission wavelength under low current, and possible flickering of the light due to unstable output power. Summary of the invention

[0004] In view of the deficiencies of the prior art, one of the objectives of the present invention is to provide a light-emitting diode epitaxial structure with lower leakage current; a second objective of the present invention is to provide a method for preparing a light-emitting diode epitaxial structure.

[0005] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0006] A light-emitting diode epitaxial structure comprises a substrate, and a nucleation layer, an unintentional doping layer, an N-type semiconductor layer, a multi-quantum well active layer and a P-type semiconductor layer which are sequentially stacked on the substrate, a blocking layer is provided between the unintentional doping layer and the N-type semiconductor layer, and a potential barrier of the blocking layer to electrons and holes is higher than a potential barrier of the unintentional doping layer to electrons and holes.

[0007] Optionally, a stress release layer is provided between the N-type semiconductor layer and the multi-quantum well active layer.

[0008] Therefore, by setting a blocking layer with a higher potential barrier to electrons than the unintentional doping layer between the unintentional doping layer and the N-type semiconductor layer, the upward propagation of defects such as dislocations can be effectively blocked, the leakage channel is reduced, and it is difficult for electrons to cross the potential barrier and penetrate into the substrate, thereby significantly reducing the leakage current.

[0009] Furthermore, the barrier layer is an aluminum gallium nitride layer. The aluminum gallium nitride layer has a small lattice mismatch with N-type semiconductor layers such as n-GaN layers and unintentionally doped layers, and can achieve coherent growth. In particular, the aluminum gallium nitride layer and GaN can achieve complete strain matching, which can be achieved by making slight changes to the existing LED epitaxial preparation process. The process is simple, highly compatible with the existing LED preparation process, and has strong applicability.

[0010] Preferably, in the barrier layer, the molar amount of aluminum is 4-30% of the total molar amount of aluminum and gallium, and more preferably 15-25%. The applicant has found that the above ratio is helpful to further improve the blocking effect. When the aluminum ratio is too low, the electron barrier is relatively low and the blocking effect is not ideal (the aluminum molar amount is 4%, the electron barrier is 30meV, and the hole barrier is 39meV, which is slightly higher than the thermoelectric potential of the semiconductor at room temperature 300K. When the aluminum molar amount is lower, hot electrons can easily cross the barrier and leak toward the substrate); when the aluminum ratio is too high, due to excessive stress concentration, cracking and other problems are prone to occur. When the aluminum molar amount is 0, the barrier is 0. When the aluminum molar amount is 26.5%, the electron barrier is 211meV and the hole barrier is 277meV, which can achieve a better electron blocking effect without affecting the epitaxial quality.

[0011] Optionally, the aluminum gallium nitride layer is doped with silicon or germanium.

[0012] Furthermore, the barrier layer is Al 0.2-0.3 Ga 0.7-0.8 N layer, further Al 0.24-0.26 Ga 0.74-0.76 N layer; preferably, the barrier layer is Al 0.265 Ga 0.735 N layer or Al 0.25 Ga 0.75 N layers.

[0013] Furthermore, the thickness of the barrier layer is 20-120 nm, preferably 40-100 nm, and more preferably 65-85 nm. The applicant has found that controlling the appropriate thickness helps to further improve the barrier effect and avoid the cracking problem of the light-emitting diode epitaxial structure. When the thickness is too small, electrons are easy to tunnel, and the barrier effect is limited; when the thickness is too large, the stress is too large and it is easy to cause cracking.

[0014] Furthermore, the thickness of the unintentionally doped layer is 500-1000nm; the thickness of the N-type semiconductor layer is 1000-3000nm, the thickness of the multi-quantum well active layer is 10-200nm; and the thickness of the P-type semiconductor layer is 40-200nm.

[0015] Furthermore, the N-type semiconductor layer is an n-GaN layer, the P-type semiconductor layer is a p-GaN layer, and the unintentionally doped layer is a u-GaN layer.

[0016] Furthermore, the substrate is a heterogeneous substrate or a homogeneous substrate; the material of the heterogeneous substrate is one of sapphire, silicon, silicon carbide, and gallium arsenide. The sapphire surface can be a c-plane, an r-plane, or an m-plane, and can also have a bias angle, such as c biased to m-plane 0-4 degrees, c biased to a-plane 0-4 degrees. The silicon carbide surface can be a C-plane or a Si-plane.

[0017] Optionally, the structure of the heterogeneous substrate can be a flat substrate or a patterned substrate. Optionally, the flat substrate can be a single-sided polished substrate or a double-sided polished substrate. The patterned substrate can be a micron-patterned substrate or a nano-patterned substrate. The pattern of the patterned substrate can be a protrusion or a pit. The pattern material of the patterned substrate can be the same as that of the substrate, or a layer of other dielectric layer, such as silicon dioxide, can be coated on the surface.

[0018] Optionally, the heterogeneous substrate is a substrate such as sapphire, silicon, silicon carbide, gallium arsenide, etc., on which a new material such as molybdenum disulfide, graphene, etc. is covered.

[0019] Optionally, the heterogeneous substrate is a sapphire, silicon, silicon carbide, gallium arsenide or other substrate covered with an aluminum nitride buffer layer by physical vapor deposition or the like, and the thickness of the aluminum nitride buffer layer is generally 20 nm.

[0020] In some embodiments, the substrate is a homogeneous substrate, and the homogeneous substrate of the gallium nitride light emitting diode is gallium nitride.

[0021] Further, the light emitting diode includes one or more of an indium gallium nitride light emitting diode, an aluminum gallium nitride light emitting diode, and an aluminum gallium indium phosphorus light emitting diode. Optionally, the light emitting diode includes an InGaN visible light LED, an AlGaN ultraviolet LED, and an AlGaInP red light LED.

[0022] Further, the barrier layer is an aluminum nitride / gallium nitride periodic structure, the aluminum nitride / gallium nitride periodic structure includes at least one aluminum nitride layer and at least one gallium nitride layer, and the aluminum nitride layer and the gallium nitride layer are alternately stacked. Preferably, in the aluminum nitride / gallium nitride periodic structure, the aluminum nitride layer is in contact with the unintentionally doped layer.

[0023] Furthermore, the number of the aluminum nitride layer is 2 to 10. Preferably, the number of the gallium nitride layer and the aluminum nitride layer is the same.

[0024] Furthermore, the thickness of the aluminum nitride layer is 0.5-20 nm, and the thickness of the gallium nitride layer is 0.5-20 nm.

[0025] Further, the barrier layer is an AlGaN / GaN periodic structure, the AlGaN / GaN periodic structure comprises at least one AlGaN layer and at least one GaN layer, the AlGaN layer and GaN layer are alternately stacked. Preferably, in the AlGaN / GaN periodic structure, the AlGaN layer is in contact with the unintentionally doped layer.

[0026] Furthermore, in the aluminum gallium nitride layer, the molar amount of aluminum is 4-40% of the total molar amount of aluminum and gallium, and the number of aluminum gallium nitride layers is 2-10. Preferably, the number of gallium nitride layers and aluminum gallium nitride layers is the same.

[0027] Furthermore, the thickness of the aluminum gallium nitride layer is 0.5-20 nm, and the thickness of the gallium nitride layer is 0.5-20 nm.

[0028] Optionally, the multi-quantum well active layer is an InGaN / GaN periodic structure, and the InGaN / GaN periodic structure includes at least one InGaN layer and at least one GaN layer, and the GaN layer and the InGaN layer are stacked at intervals, and optionally, the GaN layer is a silicon-doped GaN layer. Optionally, the GaN layer may be an AlGaN layer. Optionally, an AlN insertion layer is provided between the InGaN layer and the GaN or AlGaN layer, and the thickness of the AlN insertion layer is 1-3nm. Preferably, the number of layers of the InGaN layer and the GaN layer are both 2-20 layers, and more preferably 5-11 layers. Optionally, the thickness of the GaN layer is 8-20nm, and the thickness of the InGaN layer is 1-4nm.

[0029] Optionally, an AlGaN insertion layer is provided between the multi-quantum well active layer and the p-GaN. Preferably, in the AlGaN insertion layer, the molar amount of aluminum is 30% of the total molar amount of aluminum and gallium, and optionally, the thickness of the AlGaN insertion layer is 15nm. Optionally, the AlGaN insertion layer is a gradual change structure of aluminum molar amount, and the aluminum molar amount gradually decreases from the substrate to the surface. Preferably, the change in aluminum molar amount is gradually reduced from 30% to 3%. Optionally, an AlN insertion layer is provided between the multi-quantum well active layer and the AlGaN insertion layer, and the thickness is 1-3nm. Optionally, AlGaN can be doped with magnesium or zinc.

[0030] The method for preparing the light emitting diode epitaxial structure as described above comprises the following steps:

[0031] S1. providing a substrate;

[0032] S2, preparing a nucleation layer on the substrate;

[0033] S3, depositing and growing an unintentionally doped layer, a barrier layer, an N-type semiconductor layer, a multi-quantum well active layer, and a P-type semiconductor layer in sequence on the surface of the nucleation layer to obtain a light-emitting diode epitaxial structure.

[0034] Furthermore, in S3, metal organic chemical vapor deposition is used for deposition.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The light-emitting diode epitaxial structure of the present invention has fewer leakage channels and smaller leakage current, which helps to improve the working stability and quality of the corresponding light-emitting diode.

[0037] (2) The method for preparing the epitaxial structure of a light-emitting diode of the present invention is highly compatible with the existing preparation process of the epitaxial structure of a light-emitting diode, and does not require secondary epitaxy. Since an aluminum source is also a common configuration of a gallium nitride metal-organic chemical vapor deposition (MOCVD) device, it is only necessary to perform in-situ growth of a barrier layer at an appropriate position, which has strong compatibility, helps to reduce preparation costs, and is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a simplified structural diagram of an existing light emitting diode epitaxial structure.

[0039] Figure 2 It is a structural diagram of a light emitting diode epitaxial structure of the present invention.

[0040] Figure 3 It is a simplified structural diagram of the light emitting diode epitaxial structure of Example 1.

[0041] Figure 4 a is a transmission electron microscope image of the cross section of the light emitting diode epitaxial structure of comparative example 1.

[0042] Figure 4 b is a transmission electron microscope image of the cross section of the light-emitting diode epitaxial structure of Example 1.

[0043] Figure 5 a is an atomic force microscope surface morphology image of the unintentionally doped layer of the light emitting diode epitaxial structure of comparative example 1.

[0044] Figure 5 b is the epitaxial structure Al of the light emitting diode of Example 1 0.265 Ga 0.735 Atomic force microscope surface morphology of N barrier layer.

[0045] Figure 6 This is an energy band structure diagram of the light emitting diode epitaxial structure (LED1) provided in comparative example 1.

[0046] Figure 7 It is a diagram of the energy band structure of the light emitting diode epitaxial structure (LED2) provided in Example 1.

[0047] Figure 8 This is a comparison of the reverse leakage current mapping of LED1 (top) and LED2 (bottom) at -8 V. Position-X and position-Y represent the horizontal and vertical coordinates of the position of the core on the epitaxial structure, respectively, and the current unit is microampere.

[0048] Fig. 9 is the reverse leakage current distribution histogram of LED1 and LED2.

[0049] Fig.10 This is a comparison diagram of reverse leakage current mapping of comparative example 2 (LED3) and example 2 (LED4) at a voltage of -8 V. Wherein, position-X and position-Y respectively represent the horizontal and vertical coordinates of the position of the core particle on the epitaxial structure, and the current unit is microampere.

[0050] Fig.11 It is the reverse leakage current distribution histogram of LED3 and LED4.

[0051] Fig.12 a is an atomic force microscope surface morphology image of the unintentionally doped layer of the light emitting diode epitaxial structure of comparative example 2.

[0052] Fig.12 b is the epitaxial structure Al of the light emitting diode of Example 2 0.25 Ga 0.75 Atomic force microscope surface morphology of N barrier layer.

[0053] Fig.13 a is a cross-sectional transmission electron microscope image of the light-emitting diode epitaxial structure of comparative example 2.

[0054] Fig.13 b is a transmission electron microscope image of the cross section of the light-emitting diode epitaxial structure of Example 2.

[0055] Fig.14 This is a surface morphology image of the light-emitting diode epitaxial structure of Comparative Example 4 magnified 500 times under an optical microscope.

[0056] Fig.15 This is a surface morphology image of the light-emitting diode epitaxial structure of Example 4 magnified 500 times under an optical microscope.

[0057] Fig.16 It is an X-ray omega-2theta curve diagram of the light-emitting diode epitaxial structure of Example 4 (LED8) and Comparative Example 4 (LED7).

[0058] Fig.17 This is a surface morphology image of the light-emitting diode epitaxial structure of Example 6 magnified 500 times under an optical microscope.

[0059] Fig.18 This is a simplified structural diagram of the light-emitting diode epitaxial structure of Example 7.

[0060] Fig.19 This is a simplified structural diagram of the light-emitting diode epitaxial structure of Example 8. DETAILED DESCRIPTION

[0061] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features of the embodiments of the present invention can be combined with each other without conflict. For the convenience of description, if the words "upper", "lower", "left" and "right" appear in the following, they only indicate that the upper, lower, left and right directions are consistent with the drawings themselves, and do not limit the structure.

[0062] Example 1

[0063] See also Figure 2-3 The epitaxial structure of the light-emitting diode of this embodiment includes a substrate, a nucleation layer (low-temperature GaN layer) stacked on the substrate, an unintentional doping layer, a barrier layer, an N-type semiconductor layer, a multi-quantum well active layer and a P-type semiconductor layer. The barrier layer is an aluminum gallium nitride layer; in the barrier layer, the molar amount of aluminum is 26.5% of the total molar amount of aluminum and gallium. Specifically, the barrier layer is Al 0.265 Ga 0.735N layer. The thickness of the barrier layer is 85nm. The N-type semiconductor layer is the n-GaN layer, the P-type semiconductor layer is the p-GaN layer, and the unintentionally doped layer is the u-GaN layer. The aluminum gallium nitride layer has a higher potential barrier than GaN, and it is difficult for electrons to cross the potential barrier to penetrate into the substrate, and it can effectively block the dislocation from propagating upward, thereby reducing the number of leakage channels and reducing leakage current. The material of the heterogeneous substrate is a c-plane sapphire substrate, and its c-axis is biased 0.2 degrees toward the m direction.

[0064] In this embodiment, a metal organic chemical vapor deposition device is used to epitaxially grow the above light emitting diode structure. The metal organic chemical vapor deposition device uses an AIX 2400G3 HT metal organic chemical vapor deposition device provided by AIXTRON of Germany. The specific preparation process includes the following steps:

[0065] S1. Provide a 2-inch c-plane (0001) 430-micron thick sapphire substrate, whose c-axis is biased toward the m direction by 0.2 degrees.

[0066] S2. Unseal the substrate in the glove box and place it in the MOCVD reaction chamber. Perform surface desorption at 1050°C, with hydrogen as the carrier gas and a pressure of 200mbar for 8 minutes. After that, cool down to 530°C to deposit a 25nm GaN low-temperature nucleation layer, where trimethylgallium (TMGa) is used as the gallium source, ammonia is used as the nitrogen source, and the pressure in the reaction chamber is 400mbar. Then raise the temperature to 980°C for annealing for 6 minutes and 50 seconds. Then grow a 350nm rough layer, followed by a 300nm transition layer, and then a 1 micron recovery layer. The rough layer, transition layer, and recovery layer constitute an unintentional doping layer.

[0067] S3, reduce the pressure of the MOCVD reaction chamber to 70mbar, increase the temperature to 1100℃, switch the carrier gas to a mixture of hydrogen and nitrogen, use trimethylaluminum (TMAl) as the aluminum source, the gallium source and the nitrogen source are the same as the previous steps, and grow an 80nm thick aluminum gallium nitrogen barrier layer. The aluminum gallium ratio is controlled by controlling the source temperature and source flow rate. In this embodiment, the temperature of the TMAl and TMGa source bottles are both controlled at 17℃, the TMAl flow rate is 25sccm, and the TMGa flow rate is 10sccm.

[0068] S4. After the growth of the AlGaN barrier layer is completed, the carrier gas is switched to hydrogen, the pressure of the MOCVD reaction chamber is increased to 400 mbar, the temperature is reduced to 1050°C, and a 2-micron thick n-GaN layer is grown. The gallium source and nitrogen source are the same as in the previous step, and the dopant is disilane with a concentration of 200 ppm. The resulting n-GaN electron concentration is about 5e18 cm -3 .

[0069] S5. After the growth of the n-GaN layer is completed, the carrier gas is switched to nitrogen, the pressure in the reaction chamber is reduced to 200 mbar, the temperature is reduced to 860 °C, and triethylgallium (TEGa) is used as the gallium source to grow the first 14 nm thick quantum barrier. The quantum barrier is doped with a small amount of silicon, and the electron concentration is about 4e16 cm -3 The temperature was then lowered to 760°C, and trimethyl indium (TMIn) was used as the indium source to grow the first 2.5nm thick quantum well. Then, the remaining four pairs of quantum wells were grown repeatedly under the same conditions. Finally, a five-period InGaN / GaN quantum well active region (i.e., a multi-quantum well active layer) was formed, and the main wavelength of electroluminescence in the active region was 464nm.

[0070] S6. After the growth of the multi-quantum well active region is completed, 150nm p-GaN is grown, the temperature is raised to 980℃, the gallium source is switched to trimethylgallium, the dopant is bis(cyclopentadienyl)magnesium (Cp2Mg), and the hole concentration is about 1e17 cm -3 .

[0071] S7. After the growth is completed, the light-emitting diode epitaxial structure is taken out from the MOCVD chamber, placed in a tubular annealing furnace, and annealed at 700° C. for 20 minutes in a nitrogen atmosphere to activate the magnesium acceptor, increase the hole concentration, and obtain the light-emitting diode epitaxial structure.

[0072] A half-chip LED epitaxial structure was selected, and a 300 micron × 300 micron LED core was prepared by photolithography, etching, stripping, and electron beam evaporation of metal electrodes. The p-electrode used a Ni / Au transparent electrode, and the contact electrode used a Cr / Ti / Al metal composite layer. The thousands of LED cores prepared were measured for electrical and optical parameters using a Weiming batch point tester (LED tester ZCLED-12A10). The leakage current distribution within the chip at -8V was as follows: Figure 8 As shown in the figure for LED2, the average leakage current is 0.012 microamps.

[0073] In addition, the above steps were repeated by MOCVD until the AlGaN barrier layer was grown. The surface of the AlGaN barrier layer was characterized by atomic force microscopy (AFM) and found that the surface dislocation outcrops were significantly reduced and the roughness was also significantly reduced ( Figure 5 b).

[0074] Some light-emitting diode epitaxial structures were selected and prepared into transmission electron microscope samples by mechanical thinning and argon ion milling. The cross-section of the samples was observed by transmission electron microscopy, and it was found that the AlGaN barrier layer can effectively promote the bending and annihilation of dislocations, thereby preventing dislocations from further extending upward to the n-GaN layer and reducing the leakage channel that penetrates into the substrate direction ( Figure 4 b).

[0075] Comparative Example 1

[0076] Example 1 was repeated, except that the barrier layer was discarded and n-GaN was grown directly on the unintentionally doped layer. This was named LED1.

[0077] Table 1 is a comparison table of electrical and optical properties of the light emitting diode epitaxial structure of Example 1 and Comparative Example 1.

[0078] In addition, the above steps were repeated by MOCVD until the unintentional doping layer was grown. The surface of the unintentional doping layer was characterized by atomic force microscopy (AFM) and found that there were obvious dislocation outcrops on the surface and the roughness was relatively high ( Figure 5 a).

[0079] Table 1

[0080]

[0081] Among them, I r is the average reverse leakage current at -8V, V F is the average forward voltage at 20mA, V F3 is the average forward voltage at 0.01mA, W d is the main wavelength of electroluminescence, and LOP is the relative output power of light.

[0082] See also Figure 4 In Example 1, a layer of Al is inserted between the unintentionally doped layer (u-GaN) and the n-GaN layer. 0.265 Ga 0.735 N layer (u-AlGaN), where the barrier layer is not intentionally doped.

[0083] See also Figure 5 , the atomic force microscopy surface morphology shows that compared with the comparative example 1 ( Figure 5 a), Example 1( Figure 5 b) The surface dislocation density of the epitaxial structure is effectively suppressed, and the surface dislocation outcrops are significantly reduced, indicating that the barrier layer effectively blocks the dislocation and other leakage channels from extending upward.

[0084] The epitaxial structures of Comparative Example 1 and Example 1 were respectively made into LED chips, and Comparative Example 1 was recorded as LED1, and Example 1 was recorded as LED2. The LED chips corresponding to Comparative Example 1 and Example 1 were tested, and the results are shown in FIG. Figure 6-9 See Figure 6-7 , through the fitting of crosslight software, the barrier layer of Example 1 forms an obvious electron barrier and hole barrier between n-GaN and u-GaN, while the comparative example 1 does not have this phenomenon. Figure 8-9At a voltage of -8 V, the average reverse leakage current of Comparative Example 1 is 0.035 μA, and the average reverse leakage current of Example 1 is 0.012 μA, which is reduced by 66%, and is significantly reduced.

[0085] Example 2

[0086] Example 1 was repeated, except that the thickness of the barrier layer was 80 nm and the composition of the barrier layer was Al 0.25 Ga 0.75 N. At the same time, the growth temperature of the multi-quantum well active region is different, thus forming an active region with a shorter luminescence wavelength. That is, in S5 of its preparation process, after the growth of the n-GaN layer is completed, the carrier gas is switched to nitrogen, the pressure of the reaction chamber is reduced to 200mbar, the temperature is reduced to 870℃, and triethylgallium (TEGa) is used as the gallium source to grow the first 14nm thick quantum barrier. The quantum barrier is doped with a small amount of silicon, and the electron concentration is about 4e16 cm -3 The temperature was then lowered to 770°C, and trimethyl indium (TMIn) was used as the indium source to grow the first 2.5nm thick quantum well. Then, the remaining four pairs of quantum wells were grown repeatedly under the same conditions. Finally, a five-period InGaN / GaN quantum well active region (i.e., a multi-quantum well active layer) was formed.

[0087] In addition, the above steps were repeated by MOCVD until the AlGaN barrier layer was grown. The surface of the AlGaN barrier layer was characterized by atomic force microscopy (AFM) and found that the surface dislocation outcrops were significantly reduced and the roughness was also significantly reduced ( Fig.12 b).

[0088] Comparative Example 2

[0089] Example 2 was repeated, with the only difference being that the barrier layer was omitted.

[0090] In addition, the above steps were repeated by MOCVD until the unintentional doping layer was grown. The surface of the unintentional doping layer was characterized by atomic force microscopy (AFM) and found that there were obvious dislocation outcrops on the surface and the roughness was relatively high ( Fig.12 a).

[0091] Table 2 is a comparison of the electrical and optical properties of the epitaxial structures of the light-emitting diodes of Example 2 and Comparative Example 2. Consistent with the aforementioned theoretical conjecture, as the barrier layer becomes thinner, the Al molar amount decreases, and the blocking effect on leakage current becomes worse. Example 2 is LED4, and Comparative Example 2 is LED3. Under -8V, the average leakage current of Example 2 is 0.036 microamperes, and the average leakage current of Comparative Example 2 is 0.057 microamperes. The mapping diagram of the leakage current distribution of thousands of LED core particles in the chip is as follows: Fig.10 , the histogram is Fig.11The leakage current distribution of the barrier layer structure is significantly lower. By preparing the transmission electron microscope sample, the barrier effect of the barrier layer on dislocations was further observed using the transmission electron microscope ( Fig.13 b), the results are similar to those in Example 1. This shows the repeatability of the scheme.

[0092] Table 2

[0093]

[0094]

[0095] Example 3

[0096] Example 2 was repeated, except that the thickness of the barrier layer was 20 nm. The LED was named LED6.

[0097] Comparative Example 3

[0098] Example 2 was repeated, except that the thickness of the barrier layer was 15 nm. The LED was named LED5.

[0099] The electro-optical properties of the LEDs of Comparative Example 3 and Example 3 are shown in Table 3. As the thickness of the barrier layer decreases, the blocking ability of the electrons decreases and the reverse leakage current increases. The reverse leakage current of the LED with a 20nm barrier layer thickness is less than that of the 15nm barrier layer.

[0100] Table 3

[0101] Group Measuring the number of core particles <![CDATA[I r (μA)@-8V]]> <![CDATA[V F (V)@20mA]]> <![CDATA[V F3 (V)@0.01mA]]> <![CDATA[W d (nm)@20mA]]> LOP(au)@20mA LED5 1602 0.051±0.011 4.56±0.08 2.64±0.03 445±0.6 0.060±0.011 LED6 1523 0.046±0.017 4.60±0.11 2.65±0.05 445±0.5 0.061±0.012

[0102] Example 4

[0103] Example 2 was repeated, except that the thickness of the barrier layer was 130 nm, and the device was named LED8.

[0104] Comparative Example 4

[0105] Example 2 was repeated and named LED7.

[0106] After testing, obvious cracks appeared on the surface of Example 4 ( Fig.15 ), the satellite peak morphology in the X-ray diffraction curve of the multi-quantum well active region is also seriously deformed ( Fig.16 ), indicating that too thick causes stress accumulation and relaxation of the multi-quantum wells, affecting its luminescence and electrical properties. Since Example 4 had surface cracks, it was not prepared into an LED chip to further compare its electro-optical properties.

[0107] Fig.14 This is a morphology image of the epitaxial structure surface of Comparative Example 4 under a 500x optical microscope, and the surface is smooth and has no cracks. Fig.15This is a morphology image of the surface of the epitaxial structure of Example 4 under a 500x optical microscope, showing obvious cracks on the surface. Fig.16 The comparison of X-ray omega-2theta curves of Example 4 (LED8) and Comparative Example 4 (LED7) shows that the barrier layer is too thick, resulting in stress accumulation and relaxation of the quantum well active region.

[0108] Example 5

[0109] Example 2 was repeated, with the only difference being that the molar amount of aluminum in the barrier layer was 10% of the total molar amount of aluminum and gallium, and was named LED10.

[0110] Comparative Example 5

[0111] Repeat Example 2. Named LED9.

[0112] The electro-optical characteristics of the LEDs of Comparative Example 5 and Example 5 are shown in Table 4. As the molar amount of aluminum decreases, the blocking potential barrier for electrons and holes decreases, the electron blocking capability weakens, and the reverse leakage current increases.

[0113] Table 4

[0114]

[0115] Example 6

[0116] Example 2 was repeated, except that in the barrier layer, the molar amount of aluminum was 35% of the total molar amount of aluminum and gallium.

[0117] Comparative Example 6

[0118] Example 2 was repeated.

[0119] Fig.17 The morphology of the epitaxial structure surface of Example 6 under a 500x optical microscope shows that due to the excessively high molar content of aluminum, obvious cracks appear on the surface. This example was not prepared into an LED chip.

[0120] Example 7

[0121] The epitaxial structure of the light-emitting diode of this embodiment includes a substrate, a nucleation layer (low-temperature GaN layer), an unintentionally doped layer, a barrier layer, an N-type semiconductor layer, a multi-quantum well active layer, and a P-type semiconductor layer stacked in sequence on the substrate. The thickness of each layer except the barrier layer is the same as that of Example 2. The barrier layer is an aluminum nitride / gallium nitride periodic structure, and the aluminum nitride / gallium nitride periodic structure includes 10 aluminum nitride layers and 10 gallium nitride layers, and the aluminum nitride layers and the gallium nitride layers are stacked in sequence. Named LED12.

[0122] The thickness of the aluminum nitride layer is 3nm, and the thickness of the gallium nitride layer is 3nm. Fig.18 shown.

[0123] Comparative Example 7

[0124] Example 7 was repeated, with the only difference being that the barrier layer was discarded and n-GaN was grown directly on the unintentionally doped layer. This was named LED11.

[0125] The electro-optical characteristics of the LEDs of Comparative Example 7 and Example 7 are shown in Table 5.

[0126] Table 5

[0127]

[0128] By comparison, it can be seen that the setting of the aluminum nitride / gallium nitride periodic structure can effectively reduce the leakage current.

[0129] Example 8

[0130] Example 7 is repeated, with the only difference being that the barrier layer is an aluminum gallium nitride / gallium nitride periodic structure, the aluminum gallium nitride / gallium nitride periodic structure includes 10 aluminum gallium nitride layers and 10 gallium nitride layers, and the aluminum gallium nitride layers and the gallium nitride layers are sequentially stacked. In the aluminum gallium nitride layer, the molar amount of aluminum is 25% of the total molar amount of aluminum and gallium, and the number of aluminum gallium nitride layers is 10. The number of gallium nitride layers is the same as that of the aluminum gallium nitride layers. The thickness of the aluminum gallium nitride layer is 4 nm, and the thickness of the gallium nitride layer is 4 nm. Named LED14. The structural schematic diagram is shown in FIG. Fig.19 shown.

[0131] Comparative Example 8

[0132] Example 8 was repeated, except that the barrier layer was discarded and n-GaN was grown directly on the unintentionally doped layer. This was named LED13.

[0133] The electro-optical characteristics of the LEDs of Comparative Example 8 and Example 8 are shown in Table 6.

[0134] Table 6

[0135]

[0136] By comparison, it can be seen that the setting of AlGaN / GaN periodic structure can effectively reduce leakage current.

[0137] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A light emitting diode epitaxial structure, characterized in that: The invention comprises a substrate, and a nucleation layer, an unintentional doping layer, an N-type semiconductor layer, a multi-quantum well active layer and a P-type semiconductor layer which are sequentially stacked on the substrate, a blocking layer is arranged between the unintentional doping layer and the N-type semiconductor layer, and a potential barrier of the blocking layer to electrons and holes is higher than a potential barrier of the unintentional doping layer to electrons and holes.

2. The light emitting diode epitaxial structure according to claim 1, characterized in that: The barrier layer is an aluminum gallium nitride layer; in the barrier layer, the molar amount of aluminum is 4-30% of the total molar amount of aluminum and gallium.

3. The light emitting diode epitaxial structure according to claim 1, characterized in that: The thickness of the barrier layer is 20-120 nm.

4. The light emitting diode epitaxial structure according to claim 1, characterized in that: The barrier layer is an aluminum nitride / gallium nitride periodic structure, and the aluminum nitride / gallium nitride periodic structure includes at least one aluminum nitride layer and at least one gallium nitride layer, and the aluminum nitride layer and the gallium nitride layer are alternately stacked. 5 . The light emitting diode epitaxial structure according to claim 4 , wherein the number of the aluminum nitride layers is 2-10. 6 . The light emitting diode epitaxial structure according to claim 4 , wherein the thickness of the aluminum nitride layer is 0.5-20 nm, and the thickness of the gallium nitride layer is 0.5-20 nm.

7. The light emitting diode epitaxial structure according to claim 1, characterized in that: The barrier layer is an aluminum gallium nitride / gallium nitride periodic structure, and the aluminum gallium nitride / gallium nitride periodic structure includes at least one aluminum gallium nitride layer and at least one gallium nitride layer, and the aluminum gallium nitride layer and the gallium nitride layer are alternately stacked. 8 . The light-emitting diode epitaxial structure according to claim 7 , wherein the number of the aluminum gallium nitride layers is 2-10, and in the aluminum gallium nitride layers, the molar amount of aluminum is 4-40% of the total molar amount of aluminum and gallium. 9 . The light emitting diode epitaxial structure according to claim 7 or 8 , wherein the thickness of the aluminum gallium nitride layer is 0.5-20 nm, and the thickness of the gallium nitride layer is 0.5-20 nm.

10. The method for preparing a light emitting diode epitaxial structure according to any one of claims 1 to 9, characterized in that: The steps include: S1. providing a substrate; S2, preparing a nucleation layer on the substrate; S3, depositing and growing an unintentionally doped layer, a barrier layer, an N-type semiconductor layer, a multi-quantum well active layer, and a P-type semiconductor layer in sequence on the surface of the nucleation layer to obtain a light-emitting diode epitaxial structure.